PUBLIC PARTICIPATION PROJECTS MANAGEMENT IN THE CONTEXT OF PORTFOLIO MANAGEMENT (International Journal of Innovative Technologies in Economy, 2023)
The relevance of the research topic is due to the need for improvement and further development of scientific and methodological support for portfolio management processes in the context of the introduction of portfolio-oriented management in the field of local (territorial) self-government project management, including public participation (PP) projects.